The Role of TPQ Nurul Islam Karang Cempaka in Shaping The Character of Qur’anic Generation - Qibtiyah, Luthfatul; El-Faradis, Fayruzah (Proceeding of International Conference on Islamic Education (ICIED); Vol 4 No 1 (2019): Proceeding of International Conference on Islamic Education (ICIED), 2019)
This study aimed to describe the role of TPQ Nurul Islam Karang Cempaka in shaping the character of Qur’anic generation. The approach used is a qualitative approach, while the research is descriptive study. Data collection techniques used are observation, interview and documentation. Data analysis techniques used are data reduction, data presentation and verification. The result of this study that TPQ Nurul Islam Karang Cempaka had role in shaping the character of Qur’anic generation a) recited Qur’an well and fluently as its tajwid , b) memorized various shalawat and daily prayers, and c) habituated good morals to themselves, teachers and friends.